Permasalahan Anak Jalanan di Surabaya (Studi Eksploratif Eksploitasi Anak Jalanan di Surabaya) - Andi, Aysha Zalika Ardita Putri (Antroposen: Journal of Social Studies and Humaniora, 2022)
Abstract. This paper explored the problems of street children in Surabaya, especially the exploitation of street children. This paper has a subject to find out the causes of the emergence of street children and also the forms and causes of exploitation of street children in Surabaya. This paper was an exploratory paper with data collected through literature study. The problem in this research is examined using the household survival strategy theory by Harbirson. The results of this study indicate that there were several factors that can cause the emergence of street children, namely in the form of economic factors or poverty, family factors, and also community factors. Street children are children who are prone to exploitation. The form of exploitation of street children can be in the form of being forced to work for more than 8 hours and consuming a lot of time for street children so that they cannot do what children their age should do. The other forms of exploitation of street children are taking wages and acts of intimidation and violence carried out by parents or thugs who have power in the area where street children are doing their activites.